Friedrich Nietzsche's Thoughts on Authentic Life From an Islamic Perspective - Masita, Masita; Barsihannor, Barsihannor; Halim, Wahyuddin; Latif, Muhaemin; Abdullah`, Abdullah (Borong Newinera Publisher, 2025)
The contemporary era faces a profound crisis of identity and meaning, often characterized by nihilism, which challenges individuals to forge personal meaning in a world increasingly devoid of inherent value. This study investigates the genealogy of Friedrich Nietzsche's thought on authentic life, comparing it with the Islamic concept of Insan Kamil within the Sufi tradition to address modern alienation. Adopting a qualitative library research design, the study uses interpretation and comparative analysis of primary philosophical and key Islamic literature. This method enables in-depth examination of their conceptual convergences and divergences. The research finds that despite distinct ontological foundations, both Nietzsche's Ubermensch and the Islamic Insan Kamil emphasize self-examination, conscious living, and the active creation of meaning. Nietzsche's critique of inherited morality resonates with Islamic teachings against blind imitation and hypocrisy, while his call for authentic self-assertion parallels Sufi principles of ego-struggle and spiritual purification. This comparative analysis offers novel frameworks for understanding and potentially mitigating contemporary issues like burnout, toxic positivity, and spiritual emptiness. The study concludes that both philosophies provide robust pathways toward genuine authenticity and purpose, underscoring the urgent need for conscious, responsible living in a rapidly changing world.